Engaging Men and Boys in Violence Prevention - Flood, Michael (Global Masculinities,, 2019)
Across the globe, violence prevention initiatives focused on men and boys are proliferating rapidly. Engaging Men and Boys in Violence Prevention highlights effective and innovative strategies for the primary prevention of domestic violence, sexual violence, and other forms of harassment and abuse. It combines research on gender, masculinities, and violence with case studies from a wide variety of countries and settings. Through the cross-disciplinary examination of these varied efforts, this work will enable advocates, educators, and policy-makers to understand, assess, and implement programs and strategies which involve men and boys in initiatives to prevent violence against women.